Echocardiographic changes after cardiac resynchronisation therapy - Praus, Rudolf; Haman, Ludek; Tauchman, Miloslav; Pudil, Radek; Blaha, Vaclav; Parizek, Petr (Kardiologia polska, 2012)
BACKGROUND AND AIM: The aim of this prospective study was to evaluate echocardiographic changes in clinical responders and nonresponders after 3 and 15 months of cardiac resynchronisation therapy (CRT). METHODS: Fifty eight patients in whom a biventricular system was implanted between 2005 and 2008 were followed up at 3 and at 15 months. Clinical and echocardiography parameters including intra- and interventricular dyssynchrony were assessed at baseline and after 3 and 15 months of CRT. Every patient in whom quality of life, New York Heart Association (NYHA) class and/or 6-minute walk test (6MWT) improved (improvement of ≥ 1 NYHA class, 6MWT by more than 10%), and who was neither in hospital for heart failure nor died for cardiac reasons, was categorised as a clinical responder. RESULTS: In the responders' group, we found a significant improvement of right ventricular systolic function and a decrease in the size of the right ventricle (RV) only after 15 months (tricuspid annular plane systolic excursion [TAPSE] 17.8 ± 4.0 mm to 19.4 ± 3.7 mm, p 〈 0.05, RV diameter 29.3 ± 5.0 mm to 27.8 ± 4.2 mm, p 〈 0.05). Significant improvement of other monitored parameters occurred 3 months after CRT implantation: left ventricle (LV) end-diastolic diameter 70.5 ± 7.8 mm to 66.1 ± 8.3 mm, p 〈 0.001, LV ejection fraction 22.0 ± 5.4% to 27.1 ± 9.8%, p 〈 0.05, pulmonary artery pressure (peak gradient of tricuspid regurgitation) 37.1 ± 14.8 mm Hg to 27.6 ± 8.9 mm Hg, p 〈 0.001, tricuspid regurgitation (grade) 1.9 ± 0.9 to 1.5 ± 0.6, p 〈 0.05, mitral regurgitation (grade) 2.6 ± 0.9 to 2.2 ± 0.9, p 〈 0.001, LV dP/dt max (peak positive rate of pressure rise [slope of mitral regurgitant jet]) 482.4 ± 155.4 mm Hg/s to 981.2 ± 654.5 mm Hg/s, p 〈 0.001, velocity time integral (VTI) in LV outflow tract (LVOT) 14.1 ± 4.3 cm to 16.7 ± 4.1 cm, p 〈 0.001. In the group of nonresponders, only 2 parameters improved significantly: LV dP/dt max 561.2 ± 347.9 mm Hg/s to 1024.5 ± 745.3 mm Hg/s, p 〈 0.001, and LVOT VTI 14.5 ± 3.0 cm to 16.3 ± 2.9 cm, p 〈 0.001. Other echocardiographic parameters did not show any important changes, and no changes occurred between 3 and 15 months. On the contrary, after 15 months we saw significant progression of tricuspid regurgitation in nonresponders. In multivariate analysis, combination of baseline delay between time to peak systolic velocity in ejection phase at basal septal and basal lateral segments (Ts-lateral-septal delay) and serum creatinine was a strong predictor of clinical CRT response (area under curve was 0.80, percentage of correct decision was 82%). CONCLUSIONS: In the group of responders, significant changes of most monitored echocardiographic parameters were observed 3 months after CRT implantation. The only parameters which changed significantly after 15 months, but not previously, were the systolic function of the RV and the decrease in the RV size. In the group of nonresponders, these changes were not observed.
Keywords: následné studie; Female; Quality of Life; Follow-Up Studies; Echocardiography; kvalita života; mužské pohlaví; Heart Ventricles; koronární nemoc; trikuspidální insuficience; srdeční resynchronizační terapie; Humans; srdeční komory; zátěžový test; Coronary Disease; lidé; senioři; Exercise Test; echokardiografie; Treatment Outcome; ženské pohlaví; Ventricular Function, Right; Aged; Cardiac Resynchronization Therapy; Tricuspid Valve Insufficiency; Male; výsledek terapie; funkce pravé komory srdeční